Uranium(iv) cyclobutadienyl sandwich compounds: Synthesis, structure and chemical bonding - Tsoureas, Nikolaos; Mansikkamäki, Akseli; Layfield, Richard A. (Chemical Communications, 2020)
The 1:1 reactions of uranium(iv) tetrakis(borohydride) with the sodium and potassium salts of the cyclobutadienyl anion [C4(SiMe3)4]2- (Cb′′′′) produce the half-sandwich complexes [Na(12-crown-4)2][U(η4-Cb′′′′)(BH4)3] and [U(η4-Cb′′′′)(μ-BH4)3{K(THF)2}]2. In the 1:2 reaction of U(BH4)4 with Na2Cb′′′′, formation of [U(η4-Cb′′′′)(η3-C4H(SiMe3)3-κ-(CH2SiMe2)(BH4))]- reveals that a Cb′′′′ ligand undergoes an intramolecular deprotonation, resulting in an allyl/tuck-in bonding mode. A computational study reveals that the uranium-Cb′′′′ bonding has an appreciable covalent component with contributions from the uranium 5f and 6d orbitals.